Effects of the COVID‐19 pandemic on the outcome and mortality of patients with diabetic foot ulcer. Issue 1 (5th May 2022) - Rubin, Guy; Feldman, Guy; Dimri, Inon; Shapiro, Arthur; Rozen, Nimrod
Abstract: The outbreak of the coronavirus disease 2019 (COVID‐19) led to events that significantly impaired the treatment and management of patients with chronic diabetes. Therefore, elective treatments at hospitals were cancelled and patients with chronic ailments were instructed to stay at home and minimise the time spent in public areas. The second was due to COVID‐19‐induced anxiety that deterred many patients from seeking care and adhering to periodic out‐patient visits. In this study, we examined the short‐term effects of the COVID‐19 pandemic on patients with chronic diabetes who suffered from contaminated diabetic ulcers. We conducted a retrospective study with patients who had undergone amputations following diabetic ulcers during 2019‐2020. The research group included diabetic amputees during the COVID‐19 outbreak period ranging from March 2020 to December 2020. The control group included diabetic amputees from the corresponding period in 2019. Using the Wagner Scale, we measured the difference in the severity of ulcers upon the patient's initial admission. Additionally, we examined patient survival rates based on the size of amputations, by specifically focusing on the period between 1‐ and 6‐months post‐surgery. The results failed to suggest a clear and statistically significant worsening trend in the condition of patients in the research and control groups. Due to public lockdowns, transportation restrictions, scarcity of healthcare staff, and reduced adherence to exposure anxiety, patients with diabetic foot ulcers received inferior medical care during the COVID‐19 pandemic. However, this study could not find a statistically significant difference in the mortality and major amputation rates in patients with diabetic ulcer before and during the pandemic. The health system should incorporate the existing institutional and technological recommendations to facilitate care and follow‐up of patients with diabetic foot ulcers during the current and future pandemics.